Agency Through the We: Group-Based Control Theory. (April 2022) - Fritsche, Immo
How do people maintain a sense of control when they realize the noncontingencies in their personal life and their strong interdependence with other people? Why do individuals continue to act on overwhelming collective problems, such as climate change, that are clearly beyond their personal control? Group-based control theory proposes that it is social identification with agentic groups and engagement in collective action that serve to maintain and restore people's sense of control, especially when their personal control is threatened. As a consequence, group-based control may enable people to act adaptively and stay healthy even when personal control seems futile. These claims are supported by evidence showing increased in-group identification and group-based action intentions following reminders of low personal control. Furthermore, these responses of identifying with agentic in-groups increase people's perceived control and well-being. This article succinctly presents group-based control theory and relevant empirical findings. It also elaborates on how group-based control relates to other social-identity motives and how it may explain social phenomena.